2016
DOI: 10.1111/pan.12974
|View full text |Cite
|
Sign up to set email alerts
|

Pain after discharge following head and neck surgery in children

Abstract: Adenotonsillectomy patients represent the biggest challenge in postoperative pain management of the head and neck surgeries evaluated. The low rates of pain, nausea, and vomiting reported in the days following surgery for the other procedures suggests that children can be cared for at home with simple analgesia. Discharge information and analgesia prescribing on discharge should be tailored to the operation performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 29 publications
0
30
0
2
Order By: Relevance
“…Our research has also shown branches passing onto the lingual frenulum, confirming that the frenulum is indeed sensate. Pain requiring treatment with analgesia has been reported as long as 13 days following frenotomy (Wilson et al, ). The experience of postfrenotomy pain is likely to vary considerably between individuals, influenced by many factors including depth and size of the wound and the frequency and nature of any postprocedure wound interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Our research has also shown branches passing onto the lingual frenulum, confirming that the frenulum is indeed sensate. Pain requiring treatment with analgesia has been reported as long as 13 days following frenotomy (Wilson et al, ). The experience of postfrenotomy pain is likely to vary considerably between individuals, influenced by many factors including depth and size of the wound and the frequency and nature of any postprocedure wound interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In small children, rectal approach could be considered as well as oral paracetamol as a part of premedication (preemptive analgesia). 61,186 • Loading dose of tramadol or other suitable agent if available: nalbuphine, piritramide before the end of anesthesia.…”
Section: Intraoperative Postoperativementioning
confidence: 99%
“…• Intravenous paracetamol in immediate postoperative period or • Metamizole in divided doses. 186 • Oral NSAIDs and/or paracetamol in adequate dosage during the entire postoperative period from the moment when the oral intake is possible • Intravenous or oral tramadol or other suitable agent if available: nalbuphine, piritramide as rescue in the ward. • Consider iv-PCA including adequate monitoring 62,187 VITTINGHOFF ET AL.…”
Section: Intraoperative Postoperativementioning
confidence: 99%
“…Postoperative pain associated with myringotomy is rarely severe, with most children reporting mild-to-moderate pain scores 47. Higher pain scores may be associated with bilateral or repeat procedures.…”
Section: Discharge From Ambulatory Carementioning
confidence: 99%